Transformation Postponed: Leadership Performance and Perfomativity. Issues of Leadership in Independent Specialist Colleges - O'Brien, Kevin (2006)
The research study reported in this dissertation examines the issues of leadership and management in the independent specialist college sector. It reports on the profile of current leaders, their tasks and activities and their self assessed development needs. It also focuses on the context of leadership within the public policy context and how this has appeared to promote a new model of leadership in the public sector, one which often promotes inspirational and heroic leadership styles as the model for successful organisations. This study examines the degree to which this characterisation is either realistic or desirable within the context of Independent specialist colleges. It compares the results from this part of the further education sector in England with wider policy context with a particular focus on how a culture of performativity effects the role of leadership in raising standards.